Antiviral Effects of Lactococcus lactis on Feline Calicivirus, A Human Norovirus Surrogate - Aboubakr, Hamada A. (Food Environ Virol, 2014)
Foodborne viruses, particularly human norovirus (NV) and hepatitis virus type A, are a cause of concern for public health making it necessary to explore novel and effective techniques for prevention of foodborne viral contamination, especially in minimally processed and ready-to-eat foods. This study aimed to determine the antiviral activity of a probiotic lactic acid bacterium (LAB) against feline calicivirus (FCV), a surrogate of human NV. Bacterial growth medium filtrate (BGMF) of Lactococcus lactis subsp. lactis LM0230 and its bacterial cell suspension (BCS) were evaluated separately for their antiviral activity against FCV grown in Crandell–Reese feline kidney (CRFK) cells. No significant antiviral effect was seen when CRFK cells were pre-treated with either BGMF (raw or pH 7-adjusted BGMF) or BCS. However, pre-treatment of FCV with BGMF and BCS resulted in a reduction in virus titers of 1.3 log(10) tissue culture infectious dose (TCID)(50) and 1.8 log(10) TCID(50), respectively. The highest reductions in FCV infectivity were obtained when CRFK cells were co-treated with FCV and pH 7-adjusted BGMF or with FCV and BCS (7.5 log(10) TCID(50) and 6.0 log(10) TCID(50), respectively). These preliminary results are encouraging and indicate the need for continued studies on the role of probiotics and LAB on inactivation of viruses in various types of foods.